Głos. Uwagi na temat filmu „Nothing Compares” Kathryn Ferguson (2022) - Koschany, Rafał (Humaniora. Czasopismo Internetowe, 2025)
The starting point for this reflection is the documentary film Nothing Compares by Kathryn Ferguson, a portrait of the Irish singer Sinéad O’Connor, which—as it turned out—premiered merely a year and a half before her death (January 22, 2022 / July 26, 2023). However, this is not a conventional “life and work” portrait tracing the artist’s creative journey “from beginning to present,” but rather a selectively presented fragment of her life, with key episodes that led to the largely implied “present.” Ferguson positions O’Connor’s voice the interpretive, narrative, and existential key to this story. In the article, the term “voice” is used as a polysemous concept, allowing both the film’s director and the author of its interpretation to capture the unique phenomenon of its subject.